2020
DOI: 10.7554/elife.56236
|View full text |Cite
|
Sign up to set email alerts
|

HA stabilization promotes replication and transmission of swine H1N1 gamma influenza viruses in ferrets

Abstract: Pandemic influenza A viruses can emerge from swine, an intermediate host that supports adaptation of human-preferred receptor-binding specificity by the hemagglutinin (HA) surface antigen. Other HA traits necessary for pandemic potential are poorly understood. For swine influenza viruses isolated in 2009–2016, gamma-clade viruses had less stable HA proteins (activation pH 5.5–5.9) than pandemic clade (pH 5.0–5.5). Gamma-clade viruses replicated to higher levels in mammalian cells than pandemic clade. In ferret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(69 citation statements)
references
References 65 publications
6
63
0
Order By: Relevance
“…Consistent with this, we found that human seasonal viruses have an HA pH of fusion of 4.9-5.5 while swine H3N2 viruses have a pH of fusion >5.5. Previous work has shown a similar phenotype with human and gamma clade swine H1N1 viruses [34]. Additionally, gamma clade swine H1 viruses replicate to higher titers in MDCK cells [34], which is consistent with our observations of rPerth mutant.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with this, we found that human seasonal viruses have an HA pH of fusion of 4.9-5.5 while swine H3N2 viruses have a pH of fusion >5.5. Previous work has shown a similar phenotype with human and gamma clade swine H1N1 viruses [34]. Additionally, gamma clade swine H1 viruses replicate to higher titers in MDCK cells [34], which is consistent with our observations of rPerth mutant.…”
Section: Resultssupporting
confidence: 92%
“…As expected, the biological A/Perth/16/2009 had the same pH of inactivation (EC50 = 5.57) as the rPerth WT while the seasonal human viruses tested range in pH from 5.5 to 4.9 (Figure 3B). These data are consistent with human seasonal H1N1 viruses, which have been shown to have a pH of inactivation <5.5 [34]. The two H3N2 swine viruses tested had EC50 values that were higher (EC50 = 5.88 and 5.68) and more similar to rPerth mutant (Figure 3B).…”
Section: Resultssupporting
confidence: 83%
“…Everitt et al found that the single nucleotide polymorphism in the IFITM3 allele is related to the susceptibility to IAV [12,13]. In addition, Gerlach et al reported that the toxicity and spread of IAV are also related to the pH of the cell membrane and that the stable expression of IFITM2 and IFITM3 proteins can effectively reduce virus replication [14,15]. In this study, influenza virus replication was inhibited from HEK293 cells overexpressing hlFITM3 protein.…”
Section: Discussionmentioning
confidence: 61%
“…Everitt et al found that the single nucleotide polymorphism in the IFITM3 allele is related to the susceptibility of IAV [12,13]. In addition, Gerlach et al reported that the toxicity and spread of IAV are also related to the pH of the cell membrane, and that the stable expression of IFITM2 and IFITM3 proteins can effectively reduce virus replication [14,15]. In this study, in uenza virus replication was inhibited in HEK293 cells overexpressing hlFITM3 protein.…”
Section: Discussionmentioning
confidence: 63%